PENGEMBANGAN KAWASAN PARIWISATA DANAU TOBA, KABUPATEN TOBA SAMOSIR - Rizky Arimazona Siregar; Hanny Wahidin Wiranegara; Henky Hermantoro (Diponegoro University, 2018)
The tourism area of Toba Lake is one of The National Tourism Strategic Areas (KSPN). In the last five years the number of visitors is still low. The aim of this study is to identify the problematic aspects in developing tourism area and the efforts to overcome it. This research is quantitative and used design survey. The aspects in developing the tourism area analyzed were: tourist attraction, accessibility, infrastructure and facilities, as well as social condition and community support. All those aspects was elaborated into indicators which set to be the statements in questionnaire using Likert scale. Based on chi square test, all the aspects has different category significantly. The results showed that accessibility and community support were the aspects with the lower category than others. But, the accessibility need to be prioritised in developing the Toba Lake tourism area in Toba Samosir regency. It is required efforts to provide and improve its accessibility in developing this Toba Lake tourism area in Toba Samosir regency.